Effect of arisen dislocation density and texture components during cold rolling and annealing treatments on hydrogen induced cracking susceptibility in pipeline steel. Issue 21 (17th October 2016) - Mohtadi-Bonab, M.A.; Eskandari, M.; Szpunar, J.A.
Abstract: Abstract : In this study, we used thermo–mechanical control process (TMCP) technique to investigate the effect of arisen dislocation density and texture components on hydrogen induced cracking susceptibility in as-received API X60 pipeline steel. Dislocations and texture components appeared during cold rolling and annealing treatments. X-ray diffraction and electron backscatter diffraction measurements were used to study these phenomena. We observed that the cold rolling and annealing treatments produced higher dislocation density in deformed and recovered regions. The increase of dislocation density also caused the increased hydrogen trap density. Macro-texture studies by x-ray method indicates that initial weak texture of as-received X60 steel was changed from ζ-fiber to γ-fiber and θ-fiber in 90% cold rolled and annealed specimen. Therefore, the number of grains with 〈100〉||ND orientation which had a harmful effect on hydrogen induced cracking susceptibility increased. The 100 dominant texture and high density of hydrogen traps mitigated against any possible benefits of the other microstructural parameters such as coincidence site lattice boundaries and grain size. As a result, we could not consider this process as a suitable method to increase hydrogen induced cracking resistance in pipeline steel.